O Polimento no Design de Jogos Digitais - Um recorte da Indústria Brasileira de Desenvolvimento de Jogos - Adeline Daniele da Silva Costa (2018)
Polishment is frequently mentioned in the games industry as an element capable of significantly increasing the quality of digital games. However, there is not a single definition to the meaning and what activities are involved in this process. Considering this context, the following study was conceived to explore the ramifications of this subject. The investigation aims to identify how this topic is interpreted and which approaches are taken by professionals of brazilian games industry. The data were collected through a qualitative method using in-depth semi-structured interviews between January and May of 2018 with 13 developers from Brazil. A diversity of ideas, experiences and approaches were collected from each professional interviewed and contributed in the construction of a serie of guidelines with the best initiatives to produce a well-polished digital game. Keywords: Game Design, Digital Games, Polishment in Games Development, Polished Game Development, Games Development.